Estimating the cost of new technology products. (1st January 1999) - Colmer, Geoff; Dunkley, Martin; Gray, Keith; Pugh, Philip; Williamson, Andrew
Unfortunately, major projects employing new technologies are extremely prone to cost and timescale overruns. It is believed that this is due to two main reasons. The first is the difficulty in preparing accurate estimates. The second is that the long development cycles allow time for market conditions and customer needs to change, and these changes inevitably add to the cost. This paper presents a practical discussion on the reasons why new technology projects are especially prone to cost overruns and how projects should manage the technology and surrounding issues. In particular, an appreciation of the capabilities and limitations of cost estimates by management may help to avoid some of the poor decision-making, which contributes to cost and schedule overruns. The paper discusses some of the ideas from project and risk management for effectively introducing new technology, helping projects to successfully meet the needs of both the customers and the project itself.